2021
DOI: 10.3390/toxins13010050
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Attenuates the Progression of Renal Failure in a Mouse Model of Adenine-Induced Chronic Kidney Disease

Abstract: Nicotinamide adenine dinucleotide (NAD+) supplies energy for deoxidation and anti-inflammatory reactions fostering the production of adenosine triphosphate (ATP). The kidney is an essential regulator of body fluids through the excretion of numerous metabolites. Chronic kidney disease (CKD) leads to the accumulation of uremic toxins, which induces chronic inflammation. In this study, the role of NAD+ in kidney disease was investigated through the supplementation of nicotinamide (Nam), a precursor of NAD+, to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In unilateral urethral obstruction (UUO) mice model, NAM suppressed tubular atrophy, inflammation, and fibrosis (Zheng et al, 2019). In adenine-induced CKD mice model, NAM supplementation also reduced kidney inflammation and fibrosis and prevented the progression of kidney disease (Kumakura et al, 2021). Diabetic nephropathy (DN) is the leading cause of CKD worldwide (Alicic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In unilateral urethral obstruction (UUO) mice model, NAM suppressed tubular atrophy, inflammation, and fibrosis (Zheng et al, 2019). In adenine-induced CKD mice model, NAM supplementation also reduced kidney inflammation and fibrosis and prevented the progression of kidney disease (Kumakura et al, 2021). Diabetic nephropathy (DN) is the leading cause of CKD worldwide (Alicic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The current conclusions about the role of NAD + precursor supplementation in CKD are inconsistent. Kumakura et al (2021) demonstrated that NAM attenuated the progression of renal failure in a mouse model of adenine-induced CKD, while NR was found to not prevent CKD progression in UUO or chronic proteinuria (POD-ATTAC) mice models (Faivre et al, 2021). Both NAM and NR are first converted to NMN, and then, NAD + is synthesized under the catalysis of NMNATs.…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding that was recognized by several Nobel laureates encouraged numerous studies, in vitro and in vivo, substantiating that NAD + and its precursors are apparently beneficial in preserving organ metabolism and function and postponing aging in animal models as well as patients. 8 - 11 …”
Section: Nad + In Healthy Agingmentioning
confidence: 99%
“…This novel finding that was recognized by several Nobel laureates encouraged numerous studies, in vitro and in vivo, substantiating that NAD + and its precursors are apparently beneficial in preserving organ metabolism and function and postponing aging in animal models as well as patients. [8][9][10][11] However, many clinical trials with NAD + or its precursors (NMN and NR) showed the indefinite clinical outcomes in past years. 12 Newly, the first clinical test with oral Niacin (NA) displayed remarkable salutary effects on patients with mitochondrial myopathy.…”
Section: Nad + In Healthy Agingmentioning
confidence: 99%
“…The proximal tubule cells account for 90% of the renal cortex and are the main adenosine triphosphate (ATP) consuming cells in the kidneys ( 30 ). Under normal physiological conditions, the renal tubular epithelial cells contain abundant mitochondria ( 31 ). These cells mainly rely on fatty acids (FAs) as fuel, and they generate energy by mitochondrial oxidative phosphorylation (OXPHOS) ( 32 ).…”
Section: Introductionmentioning
confidence: 99%